Interactions in sustainable supply chain management: a framework review. Issue 1 (11th February 2019) - Yun, Gawon; Yalcin, Mehmet G.; Hales, Douglas N.; Kwon, Hee Yoon
Abstract : Purpose: The purpose of this paper is to evaluate the research conducted among the interim, dyadic interactions that bridge the stand-alone measures of economic, environmental and social performance and the level of sustainability, as suggested in the Carter and Rogers (2008) framework. Design/methodology/approach: This paper conducts a systematic literature review based on the Tranfield et al. (2003) method of the articles published in 13 major journals in the area of supply chain management between the years 2010 and 2016. Results were analyzed using an expert panel. Findings: The area of research between environmental and social performance is sparse and relegated to empirical investigation. As an important area of interaction, this area needs more research to answer the how and why questions. The economic activity seems to be the persistent theme among the interactions. Research limitations/implications: The literature on the "environmental performance and social performance (ES)" interactions is lacking in both theoretical and analytical content. Studies explaining the motivations, optimal levels and context that drive these interactions are needed. The extant research portrays economic performance as if it cannot be sacrificed for social welfare. This approach is not in line with the progressive view of sustainable supply chain management (SSCM) but instead the binary view with an economic emphasis. Practical implications: To improve sustainability, organizations need the triple bottom line (TBL) framework that defines sustainability in isolation. However, they also need to understand how and why these interactions take place that drive sustainability in organizations. Originality/value: By examining the literature specifically dedicated to the essential, interim, dyadic interactions, this study contributes to bridging the gap between stand-alone performance and the TBL that creates true sustainability. It also shows how the literature views the existence of sustainability is progressive, but many describe sustainability as binary. It is possible that economic sustainability is binary, and progressive characterizations of SSCM could be the reason behind the results favoring economic performance over environmental and social.